Isolation and identification of lactic acid bacteria in Bakasang as fermented microbe starter - Ingratubun, J Aquarista; Ijong, Frans G; Onibala, Hens (Universitas Sam Ratulangi, 2013)
Food fermentation is one of various food processing techniques that has sufficient benefits of nutrition values, and also contains lactic acid bacteria which potentially inhibit pathogenic bacteria, thus prolong shelf life of products. Bakasang is a traditional fermented food from North Sulawesi since many years ago. Reported research of bakasang previously had described that lactic acid bacteria was the dominant isolates and therefore current research aimed to isolate and identify the lactic acid bacteria which associated during fermentation day 1 and day 15, respectively. Raw materials used were 5 kg intestine and liver of skipjack brought from local market Bersehati Manado. The intestine and liver of skipjack were washed and smashed and mixed with 10% salt and 5% rice from weight of the samples and then filled into bottle to be fermented for 15 days. Every 3 days (1,3,6,9,12,15), the samples were collected and analyzed for total lactic acid bacteria by using Total Plate Count Method on de Mann Rogosa Sharpe Agar after incubation at 37°C for 24 h. The colonies grown were transferred to Tryptic Soy Broth and followed by streaking them on Tryptic Soy Agar and the free growing colony on agar medium were isolated into slant agar which were used for biochemical test such as Gram’s staining, motility test, catalase test, oksidase test, H2S test, IMVIC test (Indole, Methyl Red, Voges Proskauer, Citrate) and carbohydrate fermentation. The results showed that Lactobacillus sp., Bacillus sp., Eubacterium sp., and Bifidobacterium sp. All these four bacteria were distributed from day 1 to day 15 of the fermentation process© Fermentasi bahan pangan merupakan salah satu dari sekian banyak teknik pengolahan makanan yang mempunyai banyak manfaat dari kualitas gizi, mengandung bakteri asam laktat sehingga menghambat bakteri patogen sehingga daya simpan lebih panjang. Bakasang merupakan makanan fermentasi tradisional masyarakat Sulawesi Utara yang sudah ada sejak lama. Penelitian yang telah dilakukan terhadap bakasang menghasilkan informasi bahwa terdapat bakteri asam laktat pada bakasang sehingga menjadi tujuan untuk mengisolasi dan identifikasi bakteri asam laktat selama proses fermentasi 1-15 hari. Bahan baku bakasang ialah jeroan (usus dan hati) ikan cakalang Katsuwonis pelamis sebanyak 5 kg yang diambil dari pasar Bersehati Manado. Sampel jeroan dibersihkan kemudian dihancurkan, ditambahkan garam 10% dan nasi 5% kemudian difermentasi selama 15 hari dengan mengambil tiap-tiap sampel setiap 1, 3, 6, 9, 12, dan 15 untuk dihitung jumlah bakteri asam laktat dengan menggunakkan metode Total Plate Count pada media de Mann Rogosa Sharpe Agar dan koloni yang tumbuh di tumbuhkan kembali pada media Tryptic Soy Broth dan digores kembali pada media Tryptic Soy Agar, koloni yang tumbuh digores pada media slant agar yang selanjutnya diidentifikasi bakteri asam laktat berdasarkan uji biokimia yaitu uji pewarnaan Gram, uji motility, uji katalase, uji oksidase, uji H2S dan uji IMVIC (Indole, MethylRed, Voges Proskauer, Citrate). Hasil menunjukkan bahwa selama proses fermentasi berlangsung terdapat 4 genera bakteri asam laktat sesuai yaitu Lactobacillus sp., Bacillus sp., Eubacterium sp., dan Bifidobacterium sp., ke 4 genera ini tersebar pada fermentasi hari 1 sampai hari ke 15©